Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd006211.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive geriatric assessment for older adults admitted to hospital

Abstract: Background Comprehensive geriatric assessment (CGA) is a multidimensional, interdisciplinary diagnostic process to determine the medical, psychological and functional capabilities of a frail elderly person in order to develop a co-ordinated and integrated plan for treatment and long-term follow up. Objectives We sought to evaluate the effectiveness of CGA in hospital for older adults admitted as an emergency. Search methods We searched the Cochrane Effective Practice and Organisation of Care (EPOC) Group R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
187
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(195 citation statements)
references
References 119 publications
(96 reference statements)
3
187
0
5
Order By: Relevance
“…176,177 A Cochrane review of CGA concluded that older people were more likely to be alive and in their own home after CGA. 178 The authors suggested that wards designed for CGA seem to be more effective than mobile teams. A UK study of CGA for older people considered to be at high risk of future health problems failed to show an effect on patient outcomes or subsequent use of secondary care, but the authors concluded that this was because their intervention did not deliver truly comprehensive CGA.…”
Section: Multidisciplinary Assessmentmentioning
confidence: 99%
“…176,177 A Cochrane review of CGA concluded that older people were more likely to be alive and in their own home after CGA. 178 The authors suggested that wards designed for CGA seem to be more effective than mobile teams. A UK study of CGA for older people considered to be at high risk of future health problems failed to show an effect on patient outcomes or subsequent use of secondary care, but the authors concluded that this was because their intervention did not deliver truly comprehensive CGA.…”
Section: Multidisciplinary Assessmentmentioning
confidence: 99%
“…We considered that this preventive care should be multidisciplinary including feeding support and primary care. Feeding support and primary care for evacuated frail, disabled, or elderly people might need the same effect as consecutive intervention for the elderly people based on comprehensive geriatric assessment in the clinical settings (Ellis et al 2011), which becomes increasingly common.…”
Section: Commentarymentioning
confidence: 99%
“…30 CGA has been shown in large meta-analyses to improve outcomes for older people including improved physical and cognitive function, reduced mortality and re-admissions to hospital. 31 Its evidence-base has predominantly derived from acute hospital settings, but it also improves outcomes in community settings. 32 CGA has been described for the non-specialist reader in other publications 33 but is, in brief, a model of care driven by comprehensive assessment taking account of medical, psychological, functional, social and environmental issues.…”
Section: Complexity Of Care Home Residentsmentioning
confidence: 99%